Pembangunan Sistem Pendaftaran dan Pengurusan Pelajar Tadika Islam - Mohamad, Nur Hafiza; Mohmad Hassim, Yana Mazwin (Applied Information Technology And Computer Science, 2022)
The Islamic Kindergarten Student Registration and Management System is a web-based system that works to manage and store student information as well as facilitate the student registration process by parents through this system. Currently, the management of Tadika Islam Hira’ is still using the manual method by using the form and also the google form for the registration of new students. In fact, they also store student information in the form of file documents and Microsoft Excel software. Thus, this manual method is seen as less effective because it is more vulnerable to the risk of loss, making it difficult to find and analyze student information. Therefore, a registration and management system was developed to improve the weaknesses of the existing system. The main objective of this system is to design a system through a structured and online approach that more facilitates the registration process of new students made by parents. A prototype model-based methodology was used to develop this project. There are five phases consisting of the planning phase, analysis phase, design, implementation, and testing phase. The software used in the development of this system is Sublime and Xampp as a database. The programming languages used are Hypertext Preprocessor (PHP) and Hypertext Mark-up Language (HTML). The system is also a web-based information system that aims to receive data, store data in a database, and analyze student information. This system is used for the purpose of storing student and teacher information, financial information as well as student learning information. In general, it is hoped that this system can increase the effectiveness and efficiency of kindergarten management in managing student information and help them to manage student learning and financial information more easily.